Level and potential health risk of heavy metals in vegetables - Abd Rahim, Nazatul Adrina; Abdullah, Shakila (Penerbit UTHM, 2020)
Contamination of heavy metals in vegetables has appeared as a major concern and give high potential health risk to consumers. This study was conducted to determine the heavy metals accumulation in a different type of vegetables and different types of planting pattern. Next, this study is to analyse physic- chemical and heavy metal concentrations in vegetable using APHA standard and inductively coupled plasma spectroscopy (ICP-MS) and lastly, to assess the data obtained with standard reference of food permissible limits within certified concentration ranges. Vegetables samples were collected from different planting pattern which are from market and organic plantation at Parit Raja, Johor. The collection of samples were conducted within two months period. The samples were analysed for their pH, total organic carbon and heavy metals including Lead (Pb), Copper (Cu), Cadmium (Cd), Zinc (Zn) and Uranium (U). The determination of heavy metals was using ICP-MS. The accumulation of Cd in vegetable from the market and organic plantation was determined to be higher concentration than other heavy metals. However, the result showed that the concentration of Pb, Cu, Zn and U are within the permissible limit standard.